ETHNOGRAPHIC UNIVERSE OF ULAS SAMCHUK: FOLK TRADITIONS, PEDAGOGY AND NATIONAL IDENTITY IN THE NOVEL “MARIA” AND THE TRILOGY “VOLYN” - Багрій, Марія (SWorldJournal, 2026)
The article is devoted to the analysis of the ethnographic universe of Ulas Samchuk as one of the key ideas of his work, which combines folk traditions, pedagogical guidelines and the issue of national identity. To consider the specifics of the artistic